PENGARUH PELAYANAN PUSTAKAWAN DAN KOLEKSI BAHAN PUSTAKA TERHADAP MINAT BACA MASYARAKAT DI PERPUSTAKAAN DAERAH KECAMATAN GEMOLONG - Muthiah Kumalasari Farid; Hery Sawiji; Patni Ninghardjanti (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
The purpose of this research is to find out: (1) the influence of librarian services on the reading interests of the community in the Gemolong Subdistrict Library; (2) the influence of the collection of library materials on the reading interests of the community in the Gemolong Subdistrict Library; and (3) the influence of librarian services and collection of library materials together on the interests of reading communities in the Gemolong Subdistrict Library. This study uses correlational quantitative methods. The research population is the visitors of gemolong sub-district library in December 2020 and January 2021 which totally 886 people. Sampling technique is using simple random sampling with 133 visitors as samples. Data collection method using questionnaires, interview method, and document analysis. Data analysis is using multiple linear regression analysis with prerequisite analysis test i.e. normality test, linearity test, and multicollinearity test. The results of the study were as follows: (1) there was no significant positive influence of librarian service on public reading interests (tcount 1,779 < ttable 1.9784); (2) there is a significant positive influence on the collection of library materials on people's reading interests (tcount 3,816 < ttable 1.9784); and there is a significant influence on the service of librarians and the collection of library materials together on the reading interests of the community (Fcount 14,467 < Ftable 3.07).